DEVELOPMENT OF ANDROID-BASED INTERACTIVE MULTIMEDIA AS TEACHING MATERIALS FOR THE IC REGULATOR FILLING SYSTEM - Mulyana, Yana; Mubarak, Ibnu; Al Gifari, Muhamad Maris (Universitas Pendidikan Indonesia, 2022)
The purpose of this research is to produce android-based interactive multimedia that is feasible as a learning medium with a good response from students on the IC regulator charging system material. The method used in this study is Research and Development (RnD) with the ADDIE development model. The population in this study were students of the automotive engineering education study program and the automotive engineering concentration mechanical engineering study program. The sample in this study was 40 students of the automotive engineering education study program class of 2019. The research instrument used is a structured questionnaire. The results of the validation of the material experts get a percentage value (89%) from the learning aspect, content aspect and evaluation aspect. The results of the validation of media experts get a percentage value (91%) from the display aspect and the programming aspect. The results of student responses get a percentage score (85%) from the aspect of quality of content and objectives, aspects of instructional quality and aspects of technical quality. Interactive multimedia was declared very feasible according to material experts and media experts and received good responses from students.